2008
DOI: 10.1080/15257770701795888
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Zebularine from its 2′-Deoxyribonucleoside Triphosphate Derivative and Activity as a Template-Coding Nucleobase

Abstract: Zebularine (1-(β-D-ribofuranosyl)-1,2-dihydropyrimidin-2-one) was studied as both a 2'-deoxyribosyl 5'-triphosphate derivative and as a template incorporated into an oligonucleotide.Using a novel Pyrosequencing assay zebularine acted as cytosine analog and was incorporated into DNA with a template pairing profile most similar to cytosine, pairing with greatest efficiency opposite guanine in the template strand. Guanine was incorporated with greater affinity than adenine opposite a zebularine in the template st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Third, it is likely that when cellular DNA and RNA polymerases copy a Z-base they do so with relatively high fidelity. It should be noted that Z-base can form two Watson-Crick H-bonds with guanine and this probably the reason why DNA polymerase I Klenow fragment was found to insert a G across it more often than an A [36]. For similar reasons, Z-base may be better tolerated compared to many other base analogs by cellular proteins that interact with nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is likely that when cellular DNA and RNA polymerases copy a Z-base they do so with relatively high fidelity. It should be noted that Z-base can form two Watson-Crick H-bonds with guanine and this probably the reason why DNA polymerase I Klenow fragment was found to insert a G across it more often than an A [36]. For similar reasons, Z-base may be better tolerated compared to many other base analogs by cellular proteins that interact with nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The analogue zebularine (derived from pyrimidin-2-one) acts as a cytidine analogue, and in polymerase reactions preferentially directs the incorporation of dGMP. 162 With the pyrimidines the most modified position is C5. 125 I-labelled 5-iodo-dC has been incorporated to the end G-quadruplex structures for use in DNA footprinting to determine the effect of quadruplex-binding ligands and anticancer agents, and can be used effectively with telomeric repeats.…”
Section: Oligonucleotides Containing Modified Sugarsmentioning
confidence: 99%
“…In order to inhibit DNA methyltransferases this nucleoside must be incorporated to DNA at the GpC methylation sites. Recently it has been shown that 2'-deoxyzebularine triphosphate (dZTP) is incorporated by DNA polymerases opposite to guanine (G) and when Z is at the template it directs dGTP incorporation [5]. In spite of the absence of the amino group, 2'-deoxyzebularine behaved similar to 2'-deoxycytidine pairing with guanine [5][6][7].…”
Section: Synthesis and Hybridization Properties Of Modified Oligodeoxmentioning
confidence: 99%
“…Recently it has been shown that 2'-deoxyzebularine triphosphate (dZTP) is incorporated by DNA polymerases opposite to guanine (G) and when Z is at the template it directs dGTP incorporation [5]. In spite of the absence of the amino group, 2'-deoxyzebularine behaved similar to 2'-deoxycytidine pairing with guanine [5][6][7]. In this report we describe the melting behaviour of DNA duplexes carrying the 1, 2-dihydropyrimidin-2-one (Z) residue opposite to all four natural bases.…”
Section: Synthesis and Hybridization Properties Of Modified Oligodeoxmentioning
confidence: 99%